IDENTIFICATION OF EARLY MATURING POTATO ACCESSIONS SUITABLE FOR PROCESSING INTO CHIPS - Kumar, Raj; Mehta, A.; Kumar, V.; Bhardwaj, V. (Potato Journal, 2017)
Tuberosum (Solanum tuberosum L.) germplasm accessions (1397 in number) were evaluated for foliage maturity by recording visual observations at weekly intervals. The purpose was to identify early maturing genotypes. CP 1409 and CP 3203 were most early maturing accessions with maturity in 65-71 days after planting. Accessions CP 1408, CP 2033, CP 2101, CP 3072, CP 3366, CP 3428, and CP 3559 matured in 72-78 days after planting. Twelve accessions matured in 85 days after planting. Thirty three accessions matured in 92 days after planting. All other accessions did not mature within 92 days of planting. The accession showing maturity within 92 days were evaluated for their suitability for processing into chips and associated characters. Accessions CP 2294, CP 3647, CP 3702 CP2033 and CP 3495 were identified good for processing into chips and these can be very good parent for developing processing varieties with comparatively short duration. Other early maturing identified in present study can be used as parents in developing early maturing cultivars for other purposes.